Renter’s Insurance - Mary Harrison; Donna Davis (EDIS)
“Whether you’re a family living in a rental house or apartment, or a parent whose children are in a rental situation, one of the costs that people tend to forget or ignore is renter’s insurance. But according to consumer science researchers, everyone renting an apartment or a house should have renter’s insurance. It will protect you and your family against losses from disasters such as hurricanes and fire.” This 2-page Family Album Radio transcript was written by Mary Harrison and Donna Davis, and published by the UF Department of Family, Youth and Community Sciences, August 2012.